I can do these normally but this one has confused me.
$\displaystyle 4(3x-7)-5(2x-4)$
$\displaystyle
12x-28-10x+20=3x
$
Then I get
$\displaystyle
2x-8=3x
$
so
$\displaystyle x = -8/5$
This is wrong, why?
x is supposed to = -8
I can do these normally but this one has confused me.
$\displaystyle 4(3x-7)-5(2x-4)$
$\displaystyle
12x-28-10x+20=3x
$
Then I get
$\displaystyle
2x-8=3x
$
so
$\displaystyle x = -8/5$
This is wrong, why?
x is supposed to = -8
I assume that the starting equation is actually $\displaystyle \displaystyle 4(3x-7) - 5(2x-4) = 3x$.
You are correct up to $\displaystyle \displaystyle 2x - 8 = 3x$
$\displaystyle \displaystyle 2x - 8 - 2x = 3x - 2x$
$\displaystyle \displaystyle -8 = x$.